Ovarian Reserve and ART Outcomes in Blepharophimosis-Ptosis-Epicanthus Inversus Syndrome Patients With FOXL2 Mutations - Meng, Tingting; Zhang, Wenzhe; Zhang, Rongrong; Li, Jie; Gao, Yuan; Qin, Yingying; Jiao, Xue (Frontiers in Endocrinology, 2022)
Objective: To characterize the status of ovarian reserve and ART outcomes in BPES women and provide informative reference for clinical diagnosis and treatment. Methods: Twenty-one women with BPES were screened for mutations in the FOXL2 gene and underwent assisted reproductive technology (ART) treatment. Indicators for ovarian reserve and ART outcomes were compared between patients with and without FOXL2 mutations. Additionally, ART outcomes were compared among patients with different subtypes of FOXL2 mutations. Results: A total of 13 distinct heterozygous variants in the FOXL2 gene were identified in 80.95% of BPES women, including 4 novel mutations with plausible pathogenicity (c.173_175dup, c.481C>T, c.576del and c.675_714del). Compared to non-mutation group, patients with FOXL2 mutations had elevated levels of FSH (P=0.007), decreased AMH levels (P=0.012) and less AFC (P=0.015). They also had worse ART outcomes with large amount of Gn dosage (P=0.008), fewer oocytes (P=0.001), Day3 good quality embryos (P=0.001) and good quality blastocysts (P=0.037), and a higher cancellation rate (P=0.272). High heterogeneity of ART outcomes existed in BPES patients with different FOXL2 mutation types. Conclusions: BPES patients with FOXL2 mutations had diminished ovarian reserve and adverse ART outcomes. The genotype-reproductive phenotype correlations were highly heterogeneous and cannot be generalized. Genetic counseling for fertility planning and preimplantation or prenatal genetic diagnosis to reduce offspring inheritance are recommended.